2011
DOI: 10.1093/bioinformatics/btr526
|View full text |Cite
|
Sign up to set email alerts
|

Discovering relational-based association rules with multiple minimum supports on microarray datasets

Abstract: In the actual case study of this research, REMMAR utilized the shortest distance between any two genes in the Saccharomyces cerevisiae gene regulatory network (GRN) as the relation intensity to discover the association rules from two S.cerevisiae gene expression datasets. Under experimental evaluation, REMMAR can generate more rules with stronger relation intensity, and filter out rules without biological meaning in the protein-protein interaction network (PPIN). Furthermore, the proposed method has a higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…We also evaluated the location of ABs in a biological network derived from diverse data types such as protein-protein, gene regulatory, DNA-protein, and RNA-protein interactions, since some previous studies have indicated that mining associated gene-based patterns like association rules [4], co-expressed patterns [34] and sequential patterns [35,36] from single experiments are related in biological networks. Therefore, we chose to examine the distance between ABs in the IPA (Ingenuity® Systems, http://www.ingenuity.com) interaction network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also evaluated the location of ABs in a biological network derived from diverse data types such as protein-protein, gene regulatory, DNA-protein, and RNA-protein interactions, since some previous studies have indicated that mining associated gene-based patterns like association rules [4], co-expressed patterns [34] and sequential patterns [35,36] from single experiments are related in biological networks. Therefore, we chose to examine the distance between ABs in the IPA (Ingenuity® Systems, http://www.ingenuity.com) interaction network.…”
Section: Resultsmentioning
confidence: 99%
“…Another example is in causal SNP identification where Han et al showed that two associated SNPs in the non-coding region of CFH (complement factor H) were linked to age-related macular degeneration [3]. In our previous studies, we also demonstrated that co-expressed genes revealed from association rules are associated in yeast cells when they suffered from different stresses [4]. Therefore, many lines of evidence suggest that combination effects of certain genes influence biological outcomes rather than individual effects of a set of unassociated individual genes.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years different strategies were proposed to apply the ARM algorithm to the analysis of microarray expression data [15,16]. In this paper we use a simplified version of the ARM algorithm, which is based on two main points: (i) we look for associations containing only two genes and (ii) one of the involved genes is constrained to be the gene selected by the user (Target gene).…”
Section: Methodsmentioning
confidence: 99%
“…However, in real applications, each item can have different nature, frequency and importance, and thus there is a need to consider the nature. To address this issue, association rule mining with multiple minimum supports [6][7][8]13,14,17,21,22] and the importance of items [2,16,18,[27][28][29][30]32] were proposed.…”
Section: Introductionmentioning
confidence: 99%